Hubungan Asupan Energi, Zat Gizi Makro Dan Zat Gizi Mikro Dengan Status Gizi Pada Pegawai Di Kantor Kebangpol Kota Tangerang Selatan - Sunansyah, Elvira Putri; Harjatmo, Titus Priyo; Kamboja, Gede Ketut Wira; Wiyono, Sugeng (JGK: Jurnal Gizi dan Kesehatan, 2024)
Nutrition is a factor that influences the health and work productivity of office employees. Optimal nutritional status plays an important role in maintaining endurance, concentration and stamina while working. Several studies show the high incidence of nutritional problems among office employees in Indonesia. These problems include overweight and obesity. According to the 2018 National Riskesdas, there were 13% of employees who were obese, while in the Bamten area itself there were 32.01%. The aim of this research is to determine the relationship between energy intake, macro and micro nutrient intake and the nutritional status of employees at the South Tangerang national and political unity office. This research was conducted with a cross sectional research design. Samples were taken by random sampling. The results of the study were that most 45% were aged 21-35 years and the majority 72.5% were male, had normal weight nutritional status, adequate energy intake of 57.5%, sufficient protein of 85%, sufficient fat of 67, 5%, sufficient carbohydrates at 85%, insufficient intake of Vitamin E, namely 95%, insufficient Vitamin C, namely 70%, and insufficient calcium, namely 90%, with the results of nutritional status based on Energy and Fat getting significant results with a p value, namely 0.001 for Energy, and 0.001 for Fat, then get nutritional status results based on intake of Protein, Carbohydrates, Vitamin E, Vitamin C, and Calcium which are not significant with p results namely 0.130 for protein, 0.130 for Carbohydrates, 0.884 for Vitamin E, 0.267 for Vitamin C, and 0.832 in Calcium. In this research, the researcher provides suggestions to the Kesbangpol Office to provide education related to nutrition, as well as pay attention to the food intake consumed by employees, increase knowledge, and be able to monitor health in order to obtain maximum work productivity.Keywords: Energy Intake, Nutrients Macro, Micro Nutrients, Nutritional Status, Employess